Echocardiographic findings in left ventricular to right atrial shunts. Issue 6 (June 1977) - Mills, P; McLaurin, L; Smith, C; Murray, G; Craige, E
Abstract : The echocardiographic abnormalities of tricuspid valve motion in 2 patients with left ventricular to right atrial shunts are described. In both patients the abnormal anatomy was defined at surgery, in one patient the shunt being above the tricuspid valve leaflets (supravalvar) and in the other patient through the septal leaflet (intravalvar). Different patterns of tricuspid valve systolic fluttering were seen in these two cases and the possible reasons for this are discussed. After surgical closure of the defects the systolic fluttering of the tricuspid valve was no longer observed. Echocardiography appears to be useful in detecting the presence of left ventricular to right atrial shunts which otherwise may be difficult to diagnose.